Novel Anatomic Description of the Course of the Inferior Palpebral Vein for Minimally Invasive Aesthetic Treatments. Issue 5 (May 2016) - Lee, Sang-Hee; Lee, Hyung-Jin; Kim, Yi-Suk; Tansatit, Tanvaa; Kim, Hee-Jin
Abstract : BACKGROUND: The inferior palpebral vein (IPV) receives tributaries from the inferior palpebral part of the orbicularis oculi muscle (OOc). The aim of this study was to elucidate the venous distribution pattern of the IPV for dermal filler injection. MATERIAL AND METHODS: Fifty hemifaces from 34 cadavers were used in this study. The various distribution patterns of the IPV were classified according to its relationship with the angular vein (AV) and facial veins. RESULTS: The IPV can be classified into the following 4 types: Type I (58.0%), in which the origin of the IPV is located beneath the lateral part of the OOc; Type II (12.0%), in which the origin of the IPV is located beneath the inferior part of the OOc; Type III (8.0%), in which the origin of the IPV is located beneath both the lateral and inferior parts of the OOc; and Type IV (22.0%), in which the IPV is undeveloped. CONCLUSION: The course of the IPV can be approximated by connecting the lateral orbital rim to the C point (the meeting point between the IPV and the AV). The lateral rim can be palpated and the location of the C point is suggested as a columnar area inferior to the pupil.